2014
DOI: 10.1074/jbc.m114.564690
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Translocation Uncovers the Amyloid Peptide Aβ42 as a Regulator of Gene Transcription*

Abstract: Background: Biological activities of nontoxic A␤42 peptides remain unclear in Alzheimer disease. Results: A␤ species are taken up in the nucleus of cells by a nonregulated mechanism, but only A␤42 plays a role in gene transcription. Conclusion: A␤42 may act as a transcriptional regulator, similar to the cytoplasmic fragment AICD. Significance: Genes regulated by nuclear A␤42 could represent alternative targets for therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 66 publications
7
72
0
Order By: Relevance
“…Although their potential roles in regulating gene expression are currently not well understood, significant progress is being made. For example, we have shown that the nuclear accumulation of A␤ peptides, other than A␤42, is independent from the recruitment on gene promoters (18). We found that A␤42 and A␤42G33A accumulate equally well in the nucleus, but only A␤42 can actively regulate gene expression.…”
Section: Possible Nuclear Functions Of Aicd A␤ and Taumentioning
confidence: 82%
See 4 more Smart Citations
“…Although their potential roles in regulating gene expression are currently not well understood, significant progress is being made. For example, we have shown that the nuclear accumulation of A␤ peptides, other than A␤42, is independent from the recruitment on gene promoters (18). We found that A␤42 and A␤42G33A accumulate equally well in the nucleus, but only A␤42 can actively regulate gene expression.…”
Section: Possible Nuclear Functions Of Aicd A␤ and Taumentioning
confidence: 82%
“…These effects were specific for A␤42 and not detectable with peptides A␤43 and A␤38 or A␤42G33A, which is a substitution peptide known to form oligomeric ␤-pleated sheet complexes more readily than A␤42 WT peptide (90). Moreover, A␤42 had no effect on the expression of the Notch target HES1 (18). Although LRP1 and APP are similarly regulated as by AICD, KAI1 is downregulated by A␤42 and up-regulated by AICD.…”
Section: Possible Nuclear Functions Of Aicd A␤ and Taumentioning
confidence: 94%
See 3 more Smart Citations